Cruciferous weeds in oil seed rape – appearance and control - Klingenhagen, Günter (Julius-Kühn-Archiv, 2014)
Different cruciferous weeds were drilled in autumn 2011 and 2012 in a field near Münster. Beside common species like hedge mustard (Sisymbrium officinale Scop.), shepherd`s purse (Capsella bursa-pastoris), pennycress (Thlaspiarvense), tall hedge mustard (Sisymbrium loeselii) and flixweed (Descurainia sophia), we tried to establish weeds that are not common on arable land in Germany until now. These were: Yellow rocket (Barbarea vulgaris), hoary cress (Lepidium draba) and Turkish rocket (Bunias orientalis). In autumn 2011 emergence of the sown weeds was poor. In the second year of experiment we got good emergence of the named weeds excluding hoary cress (Lepidium draba). In autumn 2011 and 2012 different herbicidecombinations were applied across the stripes. The best results were achieved with Colzor Trio (clomazone + dimethachlor + napropamid) which was applied in pre-emergence state, a spray sequence Butisan Gold (metazachlor + quinmerac + dimethenamid-P) applied in pre-emergence followed by Salsa (ethametsulfuronmethyl) + Trend (adjuvant) in post-emergence and Clearfield-Vantiga (metazachlor + quinmerac + imazamox) + Dash (adjuvant), also applied in post-emergence state of the weeds.